Refining Employer Branding to Attract Generation Z Talent: A Case Study in an Indonesian Infrastructure SOE - Muhammad Indrahanif; Gallang Perdhana Dalimunthe; Jacob Silas Mussry (Green Publisher Indonesia, 2025)
This study aims to develop a data-driven employer branding strategy to enhance the attractiveness of a state-owned infrastructure enterprise to Generation Z (Gen Z) talent in Indonesia. Despite the company’s national significance and stable reputation, recent declines in applicant interest—particularly within the national joint SOE recruitment program—indicate a misalignment between its employer value proposition and the expectations of emerging job seekers. Using a quantitative approach, this research surveyed 205 external Gen Z respondents and 62 internal Gen Z employees. Exploratory Factor Analysis (EFA) identified five key employer branding dimensions: Organizational Attributes, Job Attributes, Workplace Attributes, Compensation & Rewards, and Social & Altruistic Value. Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed that external Gen Z candidates are primarily influenced by Compensation & Rewards. The Importance-Performance Matrix Analysis (IPMA) indicated underperformance on several critical indicators valued by Gen Z, including autonomy, inclusive culture, value alignment, and transparent evaluation. These findings suggest that the company’s current branding lacks differentiation and fails to resonate with Gen Z’s aspirations. The study contributes to the limited empirical research on employer branding within state-owned enterprises by combining external and internal perspectives and applying advanced analytical tools. Practical implications include reevaluating communication strategies, enhancing employee experience programs, and refining social value initiatives to attract and retain Gen Z talent. The proposed framework also serves as a reference for other public-sector organizations seeking to modernize their employer branding in an increasingly competitive labor market.